2009
DOI: 10.1016/j.neulet.2009.07.088
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane anesthesia interferes with the expression of cocaine-induced sensitization in female rats

Abstract: Repeated cocaine administration results in a progressive sensitization of behavior which typically occurs more readily in female rats than in males. Our recent studies of rats undergoing surgical procedures revealed that following anesthesia, females sensitized less than males receiving identical repeated cocaine injections. Since isoflurane acts primarily by increasing the effects of the inhibitory neurotransmitter γ-amino butyric acid (GABA) and reducing the effects of the excitatory amino acid glutamate, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
(24 reference statements)
1
6
0
Order By: Relevance
“…While the present results further implicate gonadal hormones and their metabolites in the sex-differences found in addiction research, more work is needed to elucidate the mechanisms driving these differences. In addition to the present findings, past result suggest that investigating neurobiological differences in GABA functions between males and females may be of interest (Campbell et al, 2002; Febo and Segarra, 2004; Siegal and Dow-Edwards, 2009). …”
Section: Discussionsupporting
confidence: 67%
“…While the present results further implicate gonadal hormones and their metabolites in the sex-differences found in addiction research, more work is needed to elucidate the mechanisms driving these differences. In addition to the present findings, past result suggest that investigating neurobiological differences in GABA functions between males and females may be of interest (Campbell et al, 2002; Febo and Segarra, 2004; Siegal and Dow-Edwards, 2009). …”
Section: Discussionsupporting
confidence: 67%
“…Then we compared the effects of systemic (Experiment 2) and intracranial (Experiment 3) GBX administration on the expression of cocaine sensitization in male and female rats. We had previously demonstrated that administration of isoflurane, which targets α4βδ GABA A receptors among others (Jia, Pignataro, & Harrison, 2007), dampens cocaine sensitization in rats (Siegal & Dow-Edwards, 2009). We therefore hypothesized that systemic administration of GBX, which is more selective than isoflurane, would affect cocaine sensitization in a similar way.…”
mentioning
confidence: 99%
“…The results of the study suggest that cocaine interferes with intra-neuronal uptake of neuromediators leading to a stepwise increase in the arrhythmogenicity of epinephrine. Other studies in different animal models showed similar effects [23][24][25][26]. About 2% of pregnancy-related DVT develops in the upper limb [25].…”
Section: Cocaine Is a Significant Problem Among Veterans Chemical Strmentioning
confidence: 57%
“…Other studies in different animal models showed similar effects [23][24][25][26]. About 2% of pregnancy-related DVT develops in the upper limb [25]. But the cases of DVT developing in association with reproductive technologies occur predominantly in the upper limb or neck in pregnant patients who had ovarian hyperstimulation syndrome [17].…”
Section: Cocaine Is a Significant Problem Among Veterans Chemical Strmentioning
confidence: 80%